N-acetylcysteine Amide Ameliorates Blast-Induced Changes in Blood-Brain Barrier Integrity in Rats - Kawoos, Usmah; Abutarboush, Rania; Zarriello, Sydney; Qadri, Aasheen; Ahlers, Stephen T.; McCarron, Richard M.; Chavko, Mikulas (Frontiers in Neurology, 2019)
Traumatic brain injury resulting from exposure to blast overpressure (BOP) is associated with neuropathology including impairment of the blood-brain barrier (BBB). This study examined the effects of repeated exposure to primary BOP and post-blast treatment with an antioxidant, N-acetylcysteine amide (NACA) on the integrity of BBB. Anesthetized rats were exposed to three 110 kPa BOPs separated by 0.5 h. BBB integrity was examined in vivo via a cranial window allowing imaging of pial microcirculation by intravital microscopy. Tetramethylrhodamine isothiocyanate Dextran (TRITC-Dextran, mw = 40 kDa or 150 kDa) was injected intravenously 2.5 h after the first BOP exposure and the leakage of TRITC-Dextran from pial microvessels into the brain parenchyma was assessed. The animals were randomized into 6 groups (n = 5/group): four groups received 40 kDa TRITC-Dextran (BOP-40, sham-40, BOP-40 NACA, and sham-40 NACA), and two groups received 150 kDa TRITC-Dextran (BOP-150 and sham-150). NACA treated groups were administered NACA 2 h after the first BOP exposure. The rate of TRITC-Dextran leakage was significantly higher in BOP-40 than in sham-40 group. NACA treatment significantly reduced TRITC-Dextran leakage in BOP-40 NACA group and sham-40 NACA group presented the least amount of leakage. The rate of leakage in BOP-150 and sham-150 groups was comparable to sham-40 NACA and thus these groups were not assessed for the effects of NACA. Collectively, these data suggest that BBB integrity is compromised following BOP exposure and that NACA treatment at a single dose may significantly protect against blast-induced BBB breakdown.